The Impact of the COVID-19 Pandemic on the Functionality of International Surgical Volunteer Organizations - Lyons, Spencer; Xu, Amy L.; Durand, Wesley M.; Patel, Shyam; Oni, Julius K.; Babu, Jacob M. (Frontiers in Surgery, 2022)
Background Surgical volunteer organizations have been severely limited during the ongoing coronavirus disease pandemic. Our purpose was to identify obstacles to surgical volunteer organizations secondary to COVID-19 and their responses. Methods Forty-one surgical volunteer organizations participated in a web-based survey (156 invited, 26% response rate). Respondents were separated into two groups: low donations surgical volunteer organizations (≤50% donations of previous year; n = 17) and high donations surgical volunteer organizations (≥75%; n = 24). Univariate analyses were used to compare the two cohorts. Results Of responding surgical volunteer organizations, 34 (83%) were unable to maintain full functionality due to COVID-19; 27% of high donations vs. 0% of low donations surgical volunteer organizations (p = 0.02). The three leading obstacles were finances/donations (78%), fewer volunteers (38%), and inadequate personal protective equipment (30%). In response, 39% of surgical volunteer organizations developed novel E-volunteering opportunities. For support, 85% of surgical volunteer organizations suggested monetary donations, 78% promotion through social media platforms, and 54% donation of personal protective equipment. Conclusion The majority of surgical volunteer organizations were unable to maintain full functionality due to stressors caused by COVID-19, including limitations on finances, volunteers, and personal protective equipment.